PENGARUH PERENDAMAN MODEL GIPSUM TIPE III DALAM LARUTAN DESINFEKTAN TERHADAP JUMLAH Pseudomonas aeruginosa - Monica Evithalia Manurung; Eddy Dahar (Dentistry Faculty, 2019)
Impression making is the main requirement to do dentures. Dental impressions become contaminated with the patients microorganisms from patients saliva, blood, pus and debris which are known as opportunistic patogens that can cross infect from the dental impressions to the gypsum casts pouredagainst them. This cross infection of microorganism remains, even after rinsing and desinfecting thegypsum casts by immersing the gypsum cast in desinfeting solutions, such as glutaraldehyde 2% orsodium hypoclorite 0,5% solutions, can be one of the way to prevent the potential of cross infectionduring dental procedures the purpose of this study is to evaluate the effect of immersing gypsum caststype III with the amount of Pseudomonas aeruginosa and the value of the surface hardness of gypsumcasts type III. The sample of this study is basedon the spesification ANSI/ADA No. 25, with three groupsof activity, with 9 samples each, which is, rinsing with distilled water (group A), immersion inglutaraldehyde 2% (group B) and immersion in sodium hypoclorite 0,5% (group C), so that totalsamples are 54 samples. Analisys with kruskal wallis and one way Anova. The number and standarddeviation of Pseudomonas aeruginosa in group A (222 74.11 CFU / mL), group B and C (0 CFU /mL). The value and standard deviation of surface hardness in group A (23.83 0.69 VHN) , group B(12.60 0.72 VHN) and C (17.24 1.14 VHN). There was an effect of immersion of gypsum type IIIwith glutaraldehyde 2% and sodium hypochlorite 0.5% on the amount of Pseudomonas aeruginosa andsurface hardness in the fabricating of dentures (p = 0.0001).Keyword: Glutaraldehyde 2%, Sodium hypochlorite 0,5%, Pseudomonas aeruginosa, Surfacehardness.__________________________________________________________________________________